Comparison od IFN-γ levels in children with tuberculosis desease(TB) and latent tuberculosis infection (LTBI). - Boshkovska, Katerina; Naceva Fustic, Stojka; Simonovska, Liljana; Dilberovska, Mirjana; Dacevski, Dragan; Popova, Gorica; Arnaudova, Ivana; Cakalarovska, Irena (ID Design Press,Skopje, Republic of Macedonia, 2018)
AIM: This study aimed to evaluate the importance of IFN-γ in the diagnosis of pediatric TB and LTBI and to compare the IFN-γ levels. METHODS: We analysed 100 patients examined for possible M. tuberculosis infection or disease at the Institute of Respiratory Diseases in Children, Kozle, Skopje. Patients were divided into 2 groups: TB disease and LTBI. The following parameters were analyzed: demographic characteristics, history of previous exposure to active TB, BCG vaccination and presence of BCG scar, lung X-ray findings, tuberculin skin test by the Monteux method and the value of INF-γ according to the Quantiferon TB gold test, direct samples of acid-alcohol-resistant bacilli of sputum and Löwenstein Jensen cultures. Informed parental consent was obtained for each child included in the study. RESULTS: In the LTBI group 60.9% had a scar from the vaccination while in the TB group 50% had BCG scar. TST induration diameters in children with or without BCG scar were significantly larger in patients with active TB. Children with active TB had significantly higher IFN-γ levels than children with LTBI. The IFN-γ for the cut-off of 0.35 IU/ml, has 64% sensitivity for detection of LTBI, versus 80.6% sensitivity for active disease. Children with close TB contact had significantly higher IFN-γ levels. Correlation between TST induration diameter and IFN-γ levels was stronger in the TB group. CONCLUSION: IFN-γ levels are significantly higher in children with active TB, and children with close contact with TB patient. It has better sensitivity in active TB. Using both tests (IFN-γ and TST) can improve the diagnose of LTBI and TB in countries where vaccination with BCG is widespread.
Keywords: children; latent tuberculosis infection; tuberculosis; tuberculin skin test; IFN-γ